2001
DOI: 10.2170/jjphysiol.51.491
|View full text |Cite
|
Sign up to set email alerts
|

ATP Suppresses the K+ Current Responses to FSH and Adenosine in the Follicular Cells of Xenopus Oocyte.

Abstract: The follicular cells of Xenopus laevis are known to have various types of receptors such as ␤-adrenergic-[1], muscarinic [2,3], , , adenosine- [8][9][10], and purinergic receptors [3,[11][12][13] in their cytoplasmic membranes. Among the agonists (transmitters or hormones) for these receptors, noradrenaline and ATP are released from sympathetic nerve endings [14], and acetylcholine is released from parasympathetic nerve endings. FSH and LH are released from the hypophysis and delivered via circulating blood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…This response is mediated by an activation of phospholipase C (PLC) and subsequent PI-turnover followed by an increase in [Ca 2+ ] i [12]. It is interesting that prior stimulation of the P2Y receptor markedly suppresses both the FSH-and Ade-induced K + -current responses, as already reported [1]. This effect is considered to be due to the phosphorylation of a signaling molecule by PKC activated after the P2Y receptor stimulation, since the direct activation of PKC by PDBu also shows a similar suppressing effect on the receptor-induced K + -current responses [1].…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…This response is mediated by an activation of phospholipase C (PLC) and subsequent PI-turnover followed by an increase in [Ca 2+ ] i [12]. It is interesting that prior stimulation of the P2Y receptor markedly suppresses both the FSH-and Ade-induced K + -current responses, as already reported [1]. This effect is considered to be due to the phosphorylation of a signaling molecule by PKC activated after the P2Y receptor stimulation, since the direct activation of PKC by PDBu also shows a similar suppressing effect on the receptor-induced K + -current responses [1].…”
mentioning
confidence: 52%
“…Thus neuronal, hormonal, and humoral controls of the follicular cells might largely affect the maturation and maintenance of the oocyte. We previously reported that the application of either a follicle-stimulating hormone (FSH) or adenosine (Ade) induces a K + -current response in the follicular cells surrounding Xenopus oocyte under voltage clamp [1]. This K + -current response is mimicked by either an intracellular application of cAMP or an extracellular application of cAMP analogue resistant to phosphodiesterase [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations suggest the existence of cell type-dependent roles for ATP. The balance of ions across the membrane is important throughout oogenesis, and hyperpolarization of the oocyte plasma membrane by activation of ATP receptors may contribute to restarting meiosis (Fujita et al, 2001;Wibrand et al, 1992). In addition, the activation of ATP receptors can depress the facilitating action of cAMP, a second messenger produced in the FCs by several stimuli (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Three main subtypes have been described: (i) A2 receptors responsive to Adenosine (Ado), coupled to cAMP synthesis and opening of K ϩ channels (cAMP-dependent K ϩ current, I K,cAMP ), that are sensitive to glibenclamide (3-7); (ii) P2Y receptors responsive to ATP and UTP that operate Cl Ϫ channels generating fast and slow Ca 2ϩ -independent currents (F Cl and S Cl ) (2,8,9); and (iii) a purinergic receptor, referred to as a P3 or novel P1 receptor, that is sensitive to both Ado and ATP and coupled to I K,cAMP generation (10,11). Also, there is a P2Y receptor that inhibits I K,cAMP and is probably the same as the receptor involved in F Cl and S Cl activation (2,12,13).…”
mentioning
confidence: 99%